Hygienic assessment of sanitary and chemical indicators of potable tap water quality in shallow water regions of Ukraine - Zorina, Olesya (ScienceRise: Biological Science, 2018)
The aim of current research was to make the hygienic assessment of sanitary and chemical indicators of potable tap water quality in Ukraine in regions with the shortage of potable water, where drinking water is used from underground low-quality sources or the big water pipelines. While conducting the research, the following methods were used: sanitary-chemical, hygienic monitoring, and mathematical statistics. It was determined, that the groundwater and hybrid water supply are used for provision of shallow water regions with potable tap water. In some regions of Ukraine, the water of centralized supply of drinking water from underground sources is of inadequate quality, which is due to the following indicators: nitrates, fluorine, dry residue, total hardness, chlorides, sulfates, iron, and manganese. Quantity of indicators for groundwater, which levels doesn’t meet the hygienic requirements, can vary from 1-2 to 6-8, in average - 6 indicators. Detected exceedances of maximum permitted hygienic requirements reach up to 2-4,6 times. With the use of combined water supply in the drinking water of consumers of the Communal Enterprise "Berdyanskvodokanal" maximum content was detected: nickel -10MAC, selen-5MAC, permanganate demand — 1,2MAC (before transporting by the big water pipeline, dry residue — 3,5MAC, total hardness—3,9 MAC, sulfates — 7,8MAC, colour — 2MAC, permanganate demand — 1,4 MAC (because of the water pollution in local surface water source). Reasonability of membrane technologies implementing for potable tap water purification has been proved. For the purpose of solving the crisis in the sphere of potable water supply considering the European legislation, the following actions need to be taken: to improve the national water legislation on water bodies protection from pollution and on assessment of potable water quality, as well as to implement the efficient modern technologies of water treatment and equip the measuring laboratories